Pertumbuhan dan Hasil Tiga Varietas Bawang Merah yang Dipengaruhi oleh Berbagai Dosis Pupuk K₂SO₄ pada Budidaya Terapung Rakit Botol - Kelvin Rizky Aryaduta Sembiring; Susilawati Susilawati; Suwandi Suwandi (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Shallots (Allium ascalonicum L.) are one of the horticultural commodities grown using a floating agriculture system. This study aims to determine the growth and yield of various shallot (Allium ascalonicum L.) varieties influenced by the application of K₂SO₄ fertilizer in floating cultivation. The research was conducted at the research pond of the Faculty of Agriculture, Sriwijaya University. This study used a factorial Completely Randomized Design (CRD) as the environmental design, consisting of 2 factors. The first factor was K₂SO₄ fertilizer, which included 4 levels: P0 (Control), P1 (60 kg/ha), P2 (90 kg/ha), P3 (120 kg/ha). The second factor was the variety of red onion plants, which included 3 levels: V1 (Bauji Variety), V2 (Bima Brebes Variety), V3 (Tajuk Variety). The red onion varieties significantly affected plant height at 8 weeks after planting (WAP) and had a very significant effect on chlorophyll content. The K₂SO₄ fertilizer dose had a very significant effect on chlorophyll content. The P2 dose or 90 kg ha⁻¹ produced the highest chlorophyll content compared to other doses. The interaction between varieties and K₂SO₄ doses had a very significant effect on chlorophyll content. However, this interaction did not significantly affect plant height, leaf number, SPAD, tiller number, and all tuber yield components. Numerically, the P2 dose or 90 kg ha⁻¹ K₂SO₄ showed the best tendency for leaf number, chlorophyll content, tiller number, and tuber dry weight. This dose increases the dry weight of the tubers by about 93.5% compared to the control.